Lefty-1 alleviates TGF-β1-induced fibroblast–myofibroblast transdifferentiation in NRK-49F cells - Zhang LJ; Zhang J; Xu CG; Zhou XJ; Wang W; Zheng RP; Hu W; Wu P (Dove Medical Press, 2015)
Lijun Zhang, Jie Zhang, Changgeng Xu, Xiangjun Zhou, Wei Wang, Renping Zheng, Wei Hu, Pin Wu Department of Urology, Renmin Hospital of Wuhan University, Wuhan, Hubei Province, People’s Republic of China Abstract: Fibroblast activation and proliferation are important for fibroblast–myofibroblast transdifferentiation, a crucial process in the pathological changes that define renal interstitial fibrosis. The left–right determination factor (Lefty) is an important cytokine of the transforming growth factor (TGF)-β family, with two variants, Lefty-1 and Lefty-2, in mice. Lefty has diverse functions, such as the regulation of embryonic development, the inhibition of TGF-β1 signaling, and the suppression of tumor activity. However, whether Lefty-1 influences fibroblast activation and proliferation, and consequently prevents fibroblast–myofibroblast transdifferentiation, remains unclear. This study aimed to investigate whether Lefty-1 can attenuate TGF-β1-induced fibroblast–myofibroblast transdifferentiation in normal rat kidney interstitial fibroblast cells (NRK-49F), as well as the mechanisms underlying any effects. Results showed that the typical fibroblast cell morphology of NRK-49F cells was altered after TGF-β1 treatment and that Lefty-1 significantly prevented this change in a dose-dependent manner. Further analyses demonstrated decreased proliferating cell nuclear antigen, cyclin D1, collagen I(A1), alpha-smooth muscle actin, and fibronectin expression. Lefty-1 further induced remarkable reductions in TGF-β1-induced Smad3 and mitogen-activated protein kinase-10/c-Jun N-terminal kinase (JNK-3) signaling, and enhanced expression of the antifibrotic factor bone morphogenetic protein (BMP)-5. However, without TGF-β1, Lefty-1 had no effect on Smad3, JNK-3, and BMP-5 activation and fibroblast–myofibroblast transdifferentiation. Taken together, these findings indicate that Lefty-1 can alleviate TGF-β1-mediated activation and the proliferation of fibroblasts. Furthermore, Lefty-1 may prevent fibroblast–myofibroblast transdifferentiation in part via modulations of Smad3, JNK-3, and BMP-5 activities in the TGF-β/BMP signaling pathway. Keywords: Lefty-1, NRK-49F, fibroblast, myofibroblast, transdifferentiation